If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -43 = 48 + -8x Reorder the terms: -43 + -1x = 48 + -8x Solving -43 + -1x = 48 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -43 + -1x + 8x = 48 + -8x + 8x Combine like terms: -1x + 8x = 7x -43 + 7x = 48 + -8x + 8x Combine like terms: -8x + 8x = 0 -43 + 7x = 48 + 0 -43 + 7x = 48 Add '43' to each side of the equation. -43 + 43 + 7x = 48 + 43 Combine like terms: -43 + 43 = 0 0 + 7x = 48 + 43 7x = 48 + 43 Combine like terms: 48 + 43 = 91 7x = 91 Divide each side by '7'. x = 13 Simplifying x = 13
| 111x+7=118 | | 4n+1+a-11=0 | | x+5x+7=25 | | vx*2=25 | | -7=7x+x^2 | | 3x^3+32x^2+64=0 | | B=495(1+0.04)2+2 | | v*2=25 | | In(x+3)=In(2)+In(15) | | 2k^2+4k=63 | | In(x+3)=In(2)+(15) | | 3(y-3)=2y-9+6 | | 81+16k^2= | | 4t+7=3t-1 | | 16=4v | | 3/2x=-7/8 | | 1/9x5 | | B=1,000(1+0.02)10+10+10+10+10+10+10+10+10+10 | | y-8=2(x+6) | | B=1,000(1+0.02) | | -25=6m-m | | 12x+4=7x+14 | | x+3x=56 | | y=3/5x-9 | | q(25)=100-4*25 | | -5/8x=-40 | | 4(3n-2)=(5n+3)+1 | | 4p^2-16p=-16 | | 5x+1y=35 | | 18-2(m+7)=-2 | | 8-5r+8r-6=10r-11+2r | | 4x-5(x+2)=2x-3(x+1) |